Spi-ku : a clutter of short verse on eight legs - Bulion, Leslie, 1958- (Peachtree, 2021)
Relates facts and information about fifty different types of spiders through fourteen short poems that range in style and call out spiders' abilities, characteristics, and behaviors. Includes a glossary of science terms, a description of poetic forms, a spider-hunt activity, resources for further study, and a size chart.